Bronchoalveolar Lavage in Interstitial Lung Disease: A Narrative Literature Review - Romadani, Rizki; Sri Indah Indriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Establishing a diagnosis of interstitial lung disease (ILD) is very important because the diagnosis of ILD is often missed with other lung diseases. Apart from clinical diagnosis of ILD, other tests are also required, such as a lung biopsy, which can be done using open lung biopsy but has high mortality and morbidity rates. Apart from that, lung biopsy can be done using video-assisted thoracoscopy (VATS) and transbronchial biopsy, but it is relatively more expensive compared to examination bronchoalveolar lavage (BAL), which is another diagnostic approach of ILD. Bronchoalveolar lavage is performed using a flexible fiber bronchoscope (fiberoptic bronchoscopy), which has a lower morbidity and mortality rate.